(untitled) (Hungarian Journal of Industry and Chemistry, 2001)
In this paper the object is a life-cycle assessment (LCA) of a pharmaceutical product. The target of the analysis is to compare different packaging alternatives from environmental aspect. The product is an antidepressive produced by one of the leading Hungarian pharmaceutical factories. In the market the product appears as injection and as a pill packaged in two different ways, in glass bottle and in blister (aluminium and plastic foils laminated together). These three systems: injection, glass and blister are compared in this paper using LCA.